Association between weight change and remission of type 2 diabetes: a retrospective cohort study in primary care - Dambha-Miller, H; Hounkpatin, H; Stuart, B; Farmer, A (Wiley, 2021)
The purpose of this study was to quantify the association between weight change and the likelihood of remission of type 2 diabetes in a population-based cohort without intensive interventions.